Peningkatan Orientasi Kewirausahaan dan Inovasi Produk pada UMKM Percetakan di Surabaya - Fajar Basroni, Naam; Wahyu Susanto, Iwan (Universitas Merdeka Surabaya, 2023)
The printing industry in Indonesia is experiencing major changes with the adoption of digital technology. Even though traditional businesses have switched to digital media, challenging market conditions and tough competition from online businesses have resulted in the growth of the printing industry in Indonesia only reaching 5% in 2018. Therefore, community service research was conducted to increase entrepreneurship and product innovation in one of the MSMEs in the printing sector in Surabaya. The research, which was conducted from November 2022 to February 2023, used observation and interview methods to obtain comprehensive information about business practices, entrepreneurial orientation, and product innovation mentoring methods, as well as to help improve entrepreneurial knowledge and skills. The results of this study are, the owner of a printing MSME decided to change their business focus to printing labels, stickers and barcodes using the proceeds from sales of old printing machines and bank loans, and successfully evolved into a printing business with a legal entity CV.